AN EXPLORATORY STUDY ON DETERMINANT OF HEALTH FINANCING BY HOUSEHOLD IN MALAYSIA - Hirnissa, M. T.; Zariyawati, M. A.; Diana-Rose, F (International Journal of Accounting, Finance and Business, 2018)
Health financing was introduced in Malaysia to allocate the funds for health care population groups and specific types of health care. However, nowadays Malaysia are facing the rising costs of living which also consist cost for health care. This has brought the effect of decreasing of the investment in health financing among Malaysian. The objective of this research is to analyze the determinants of households' health financing in Malaysia. This research is conducted using survey questionnaire to Malaysia resident that have income. Data collection from the distribution of the questionnaire was analyzed by using the Statistical Package for Social Science (SPSS) 21.0. Three groups of determinants are tested, which include demographic factors, job factors and external factors. By using multiple regression analysis, the result shows that five independent variables are recognised as having the incredible effect on the households’ health financing in Malaysia. Gender, age, level of education, monthly income and family and friends influence have significant relationship towards households' health financing in Malaysia.